The Effects of Field-of-Education Job Mismatch on the Current Earnings of the Recent Graduates of the University of Gambia - Jaiteh, Lala; Xin, Gong; Sidibe, Abou (Advances in Social Sciences Research Journal, 2024)
Access to decent and well-paid jobs is increasingly challenging for many college graduates. As a result, these graduates often turn to "nonstandard" employment, which is typically outside their field of study. This study examined the impact of field-of-education-job mismatch on the current earnings of recent graduates from the University of the Gambia. It specifically investigated how working in mismatched jobs has affected their earnings. The research focuses on the 2016-2019 cohort of graduates from the School of Arts, Sciences, and Humanities at the University of the Gambia. An explanatory sequential mixed-method design was used to examine the effects of field-of-education-job mismatch on these graduates. The quantitative phase consisted of three hundred (n=300) graduates who were selected through the use of simple random selection techniques, while the qualitative phase consisted of twenty (n=20) cases who were purposively selected from the quantitative phase based on the severity of the mismatch. The Chi-square analysis and multivariate linear regression analysis were used to ascertain the effects of field-of-education-job mismatch on the current earnings of the graduates. The results obtained from the quantitative phase revealed that the self-evaluation of participants who are currently working showed that more than half (56.4%) of the participants indicated that their field-of-study did not at all match with their current job. Only 13.3% indicated that their field of study perfectly matched their current job. The analysis showed one variable significantly related to current earnings (income) at p<0.05. However, two more variables (females and Ph.D. graduates) showed a significant relationship with current earnings among graduates at p<0.1.